Medical School and Stress: A Cross-sectional Study of Stress among Medical Students in Uttar Pradesh University of Medical Sciences in district Etawah - Krishnappa, Kiran; Singh, Naresh Pal; Jain, Pankaj Kumar; Sharma, Ankita; Mehra, Jyoti; Nayak, Kripa Shankar (Indian Journal of Community Health, 2018)
Background: Medical education has come long way since the era of Hippocrates. It is progressively evolving into a more organized and complicated system. All over the world, Medical education is criticized as one of the most demanding and stressful academics, showing effects on physical and mental health of medical students. This research was conducted to study stress and its factors in students of UPUMS, Saifai, Etawah, Uttar Pradesh. Aim & Objectives: To estimate the prevalence of stress among medical students of UPUMS. To estimate internal consistency of Medical Students Stress Questionnaire (MSSQ-40). Material & Methods: A Cross-sectional study was carried out during Oct. 2017 - Mar. 2018 among MBBS Students of all academic years in Uttar Pradesh University of Medical Sciences (UPUMS), Saifai. All the students enrolled in the university available on the day of data collection were recruited in the study. MSSQ-40 was the study tool to assess stress. Ethical clearance was obtained from Ethical Committee. Statistical analysis done in SPSS-23. Results: The mean age of subjects was 22.4±2.3 years, more than 84% of the respondents had moderate and high stress. More number of females perceived stress than the male, 33% female were suffering from high & severe stress. statistically significant. Conclusion: Gender & grades had clear association with stress, academics & interpersonal relation caused more stress. Early detection and effective intervention can prevent future illness among medical students.